Review of New Zealand Coastal Talitroids with description of three new genera (Crustacea, Amphipoda, Senticaudata) - Hughes, Lauren E.; Lowry, James K. (Zootaxa, 2023)
A generic revision is provided for the New Zealand coastal talitroids, which reports two families, seven genera and thirteen species. Three new genera are described: Aotearorchestia gen. nov.; Subantarctorchestia gen. nov.; and Tatahipeke gen. nov. to accommodate seven known species, A. chathamensis (Hurley, 1956) comb. nov.; A. telluris (Spence Bate, 1862) comb. nov.; S. aucklandiae (Spence Bate, 1862) comb. nov.; S. bollonsi (Chilton, 1909) comb. nov.; Tatahipeke cookii (Filhol, 1885) comb. nov.; T. kirki (Hurley, 1956) comb. nov.; and T. tumida (G.M. Thomson, 1885) comb. nov. The three genera, Bellorchestia Serejo & Lowry, 2008, Protorchestia Bousfield 1982 and Transorchestia Bousfield, 1982 are revised to include additional information on morphology, growth stages and distributions for three New Zealand species: Bellorchestia quoyana (Milne Edwards, 1840); Transorchestia miranda (Chilton, 1916); and Trans. serrulata (Dana, 1852a). Lastly, a small commentary is given on four species of coastal talitroids where additional museum collections could not be located for study, B. spadix (Hurley, 1956), Pictonorchestia dentata (Filhol, 1885), Protorchestia campbelliana (Bousfield, 1964), and T. kirki (Hurley, 1956) gen. et comb. nov. A dichotomous key and pictorial field guide are provided to all New Zealand coastal talitroids.